Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose SMARCB1-deficient renal medullary carcinoma (RMC) is an ultra-rare, lethal malignancy refractory to therapies approved for other renal cell carcinomas, and its rarity makes randomized trials logistically unfeasible. We investigated whether wild-type epidermal growth factor receptor (EGFR) is a therapeutically actionable dependency in RMC and translated this insight into a deployable clinical regimen. Experimental design EGFR expression was assessed by CLIA-certified immunohistochemistry in RMC tumors and by integrated RNA- and chromatin immunoprecipitation-sequencing of primary tumors and adjacent kidney. Panitumumab was compared with erlotinib in patient- and cell line-derived xenografts, and its mechanism defined by immunoblotting, confocal colocalization, cell-cycle and apoptosis assays, and natural killer (NK) cell co-culture. Panitumumab-based therapy was then evaluated prospectively in 26 patients with RMC across ten centers on two continents. Results RMC showed uniformly high membranous EGFR (median H-score 300), with enhancer and promoter reprogramming at the EGFR locus and a ligand switch from EGF to epiregulin and amphiregulin. EGFR expression was uncoupled from SMARCB1 status in vitro. Panitumumab outperformed erlotinib in RMC xenografts, suppressed AKT and ERK1/2 signaling, and routed EGFR to LAMP1-positive lysosomes in vitro; its effect was predominantly cytostatic, with minimal NK cell-mediated cytotoxicity. Clinically, panitumumab-based therapy achieved a 53.9% objective response rate, including 15.4% complete responses, with median progression-free and overall survival of 5.8 and 9.5 months. Conclusions Wild-type EGFR is a foundational dependency in RMC that is effectively targeted by panitumumab-based therapy. These findings, derived from a non-randomized registry, provide a biological and clinical rationale for further prospective validation.